Oblikovalna tožba za zmanjšanje pogodbenih obveznosti - Georgievski, Tina (Pravnik, 2014)
Concerning their goal, there are three different types of constitutive rights in the field of contractual law: those aiming to create, terminate and/or change a contractual relationship. The latter are forming or "modificational" constitutive rights. There are two ways to enforce a constitutive right, by a statement of the holder to the other party and by a constitutive action. The constitutive effect, which is the effect of changing an obligation of a party or the whole contractual relationship, occurs in the former case when the other party receives the statement and in the latter case with the finality of the constitutive judgment. The manner of enforcement of constitutive rights is prescribed by the Slovene Code of Obligations. It regulates their creation, among others, in the situation of change of circumstances, which has occurred after the time of signing of a contract (e.g. the agent has done little or almost no work at all in selling a house and the agreed commission is in the eyes of the principal excessive, so he wants the judge to reduce it). Even the right to reduce the disproportionate liquidated damages or earnest, agreed by the parties, as an exception of pacta sunt servanda, is a constitutive right. Likewise are the rights to reduce the price in consequence of a defective product or service (actio quanti minoris). The manner of enforcement of constitutive rights is not very clear and varies from bare objection, raised against the claim of the plaintiff, to the constitutive action before the court. When the law prescribes the three basic elements of a constitutive right: (1) the right of a party to claim, (2) the disproportion or unfairness of contractual obligation and (3) the role of the court to decide about the claim, even if it is implicit, a constitutive action should be filed in a court to enforce a constitutive right. Even in such cases the parties have the power to change their contractual relationship if both are willing to do so. In lack of consensus, the holder's obliged to file a constitutive action to enforce his right to change his obligation or contractual relationship. Bare objection should not be treated as a successful way to enforce a constitutive right prescribed by law as a right that has to be enforced through a court's judgment. The constitutive effect in these cases can be produced solely by a constitutive judgment and not otherwise.
Keywords: obligacije; pogodbe; pogodbeno pravo; tožbe